Resilient Leaders and Institutional Reform: Theory and Evidence. (October 2016) - Besley, Timothy; Persson, Torsten; Reynal‐Querol, Marta
Abstract : Strengthening executive constraints is one of the key means of improving political governance. This paper argues that resilient leaders who face a lower probability of being replaced are less likely to reform institutions in the direction of constraining executive power. We test this idea empirically using data on leaders since 1875 using two proxies of resilience: whether a leader survives long enough to die in office, and whether recent natural disasters occur during the leader's tenure. We show that both are associated with lower rates of leader turnover and a lower probability of a transition to strong executive constraints. This effect is robust across a wide range of specifications. Moreover, in line with the theory, it is specific to strengthening executive constraints rather than generalized political reform.